2020
DOI: 10.33788/rcis.71.17
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Information Disclosure of Social Networking Site on Consumers’ Food Safety Perception in Tourism Factories

Abstract: Incidents relative to food safety issues have damaged consumers’ trust in these food providers as well as their purchase intention. Hence, it is important to regain this trust and regain consumers’ purchase intention. Information regarding products and food providers plays an essential role in enhancing consumers’ trust in food safety. A total number of 398 valid survey samples was analysed by using the analytical methods of PROCESS. Accordingly, the results of this article indicate that trust in food safety m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Pengetahuan produk yang dimiliki oleh konsumen telah diakui sebagai karakteristik yang memengaruhi semua fase dalam proses pengambilan keputusan (Bettman dan Park, 1980;Chuang et al, 2020). Konsumen dengan tingkat pengetahuan produk yang berbeda akan memiliki persepsi yang berbeda pula terhadap suatu produk (Laroche et al, 2003;Baker et al, 2002;Blair dan Innis, 1996).…”
Section: Pengetahuan Produk (Product Knowledge)unclassified
See 1 more Smart Citation
“…Pengetahuan produk yang dimiliki oleh konsumen telah diakui sebagai karakteristik yang memengaruhi semua fase dalam proses pengambilan keputusan (Bettman dan Park, 1980;Chuang et al, 2020). Konsumen dengan tingkat pengetahuan produk yang berbeda akan memiliki persepsi yang berbeda pula terhadap suatu produk (Laroche et al, 2003;Baker et al, 2002;Blair dan Innis, 1996).…”
Section: Pengetahuan Produk (Product Knowledge)unclassified
“…Tingkat pengetahuan produk yang dimiliki oleh konsumen dapat memengaruhi informasi dan perilaku pengambilan keputusan (Brucks, 1985;Park, Mothersbaugh, & Feick, 1994). Terdapat dua konstruk mengenai pengetahuan tentang produk (Brucks, 1985;Park et al, 1994;Chuang et al, 2020). Pertama adalah pengetahuan obyektif, yaitu informasi akurat mengenai suatu produk yang tersimpan dalam memori jangka panjang.…”
Section: Pengetahuan Produk (Product Knowledge)unclassified
“…The emergence of food safety is impacting a country's economic performance as food safety concerns could reduce consumer willingness to buy. After a food safety incident in Taiwan caused by contaminated oil in 2014, the total turnover of the food industry had fallen by 4.8% from the previous month (Chuang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Existing research, primarily identified through Scopus and Web of Science databases, has empirically examined the factors individually, neglecting their interconnectedness between the identified impact on consumer behaviour. While some studies have emphasised the significance of trust in food safety (Chuang et al, 2020;Wang & Yueh, 2020) or perception of risks (Cembalo et al, 2019;Quevedo-Silva et al, 2020) and benefits (Fleseriu et al, 2020), others have focused on product features like labelling and branding (Legendre & Coderre, 2018), or consumer characteristics such as knowledge (Wekeza & Sibanda, 2019) and socio-demographics (Baiyegunhi et al, 2018). However, there is a notable gap in the literature regarding the comprehensive analysis of how these factors collectively influence consumers' decisions to purchase safe food.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers across the globe are working to establish a relationship between social media communications on the part of the organizations or through created user groups and the response behavior shown by the customers in the form of engagement, enhanced trust, and continued loyalty (Chu & Kim, 2011; Chuang et al, 2020; Jahng & Hong, 2017). Financial well-being in terms of good financial product selection can also be reached by creating desired financial behavior through financial guidance via social media platforms, according to previous studies (Cwynar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%